Protective effect of the Rubus chingii Hu. fruit extract on ultraviolet B-induced photoaging via suppression of mitogen-activated protein kinases (MAPKs) in vitro - She, Jie-Mei; Yuan, Hui-Hui; Zhang, Jin; Si, Zhao-Nian; Lan, Min-Bo (Archives of Biological Sciences, 2019)
Paper description: Rubus chingii Hu possesses antioxidant, anti-inflammatory and anti-aging activities. The ethanol extract of the fruit (E-EA) demonstrated significant anti-photoaging properties in UVB-induced human fibroblast (HFF-1) cells, observed as a decrease in levels of reactive oxygen species (ROS), inhibition of matrix metallopeptidase 1 (MMP-1) production, and promotion of type-I procollagen production via suppression of the mitogen-activated protein kinase (MAPK) signaling pathway. E-EA is suggested as a potential anti-photoaging agent for the protection of skin from UVB damage. Abstract: Rubus chingii Hu. is an important traditional Chinese medicine with a beneficial effect on the kidney. Traditional Chinese medicine theory believes that supporting the kidney has a key role in anti-aging. To the best of our knowledge, the anti-photoaging activity of Rubus chingii Hu. has not been investigated. We investigated the anti-photoaging effects and the underlying mechanism of the ethyl acetate fraction of Rubus chingii Hu. fruit ethanol extract (E-EA) in UVB-induced human fibroblasts (HFF-1). Our results show that E-EA (10-40 μg/mL) displayed preventive and therapeutic effects on UVB-induced cytotoxicity in HFF-1 cells. E-EA also presented significant anti-photoaging properties in UVB-induced HFF-1 cells by decreasing the levels of reactive oxygen species (ROS), inhibiting matrix metallopeptidase 1 (MMP-1) production and promoting type-I procollagen production via suppression of the mitogen-activated protein kinase (MAPK) signaling pathway. These results suggested that E-EA might be a promising anti-photoaging agent to protect the skin from UVB damage, with a potential application in cosmetics. https://doi.org/10.2298/ABS190321038S Received: March 21, 2019; Revised: May 3, 2019; Accepted: June 3, 2019; Published online: July 7, 2019 How to cite this article: She J, Yuan H, Zhang J, Si Z, Lan M. Protective effect of the Rubus chingii Hu. fruit extract on ultraviolet B-induced photoaging via suppression of mitogen-activated protein kinases (MAPKs) in vitro. Arch Biol Sci. 2019;71(3):541-50.